THE COMPARISON OF EFFICIENCY OF THE CAPITAL ASSET PRICING MODEL, THE FAMA-FRENCH THREE-FACTOR MODEL AND THE FAMA-FRENCH FIVE-FACTOR MODEL FOR ENERGY AND UTILITIES IN THE STOCK EXCHANGE OF THAILAND - Kusolchan, Supisara; Pongsupatt, Tharinee (Journal of Buddhist Education and Research (JBER), 2023)
The objective of this study was to compare the performance of the Capital Asset Pricing Model (CAPM), the Fama-French Three-Factor Model and the Fama-French Five-Factor Model in explaining excess rate of returns for Energy and Utilities in the Stock Exchange of Thailand. A group of 17 stocks from the Energy and Utilities that are registered in the Stock Exchange of Thailand during the period from 2012 to 2021 was chosen as a sample for this study. The result shows that the Fama-French Five-Factor Model is the best model in explaining the variation of excess returns with the average Adjusted R2 equals to 73.45%. The second model is the Fama-French Three-Factor Model which can explain the variation of excess returns with the average Adjusted R2 equals to 30.85%. The third model is the Capital Asset Pricing Model (CAPM) which can explain the variation of excess returns with the average Adjusted R2 equals to 20.30%. The intercept-test result also shows that the independent variables of the Fama- French Five-Factor Model are able to capture the variation of excess rate of return in 14 out of 15 portfolios, while the Fama-French Three-Factor Model can capture the variation of excess rate of return in 13 out of 15 portfolios and the Capital Asset Pricing Model (CAPM) can only capture the variation of excess rate of return in 12 out of 15 portfolios. These results agree with the intercept of GRS Test that the CAPM, Three-Factor and Five-Factor of Fama- French cannot explain the variation of excess rate of return in all portfolios.